Anionic hexadeca-carboxylate tetrapyrazinoporphyrazine: synthesis and in vitro photodynamic studies of a water-soluble, non-aggregating photosensitizer. Issue 12 (26th January 2016) - Machacek, Miloslav; Kollár, Jan; Miletin, Miroslav; Kučera, Radim; Kubát, Pavel; Simunek, Tomas; Novakova, Veronika; Zimcik, Petr
Abstract : Photodynamic activity of hexadeca-carboxylate tetrapyrazinoporphyrazine is largely influenced by intracellular pH and its interaction with serum proteins. Abstract : A sodium salt of zinc tetrapyrazinoporphyrazine bearing eight 3, 5-dicarboxylatophenyl substituents (1 ) was synthesized. The presence of sixteen negative charges in a rigid arrangement on the periphery of the macrocycle inhibited its aggregation in water or buffers at pH > 5.8. Strong aggregation was, however, observed in buffers at pH < 4.8 due to the protonation of carboxylate functions. Fluorescence microscopy revealed that the compound localized to lysosomes and endosomes in cells. The compound's photodynamic activity on HeLa cancer cells (IC50 = 5.7 ± 1.1 μM) was found to be influenced by both pH and interactions with serum proteins. This was demonstrated with a detailed in vitro study based on the inhibition of vacuolar H + -ATPase using bafilomycin A1, which increased the intracellular fluorescence of1 . Compound1 also formed interactions with serum proteins that partially quenched its excited states; however, they also protected the compound from self-aggregation at low pH.